1990
DOI: 10.1159/000177571
|View full text |Cite
|
Sign up to set email alerts
|

Estimation de la consommation moyenne de fibres alimentaires en France

Abstract: The recent progress in the knowledge of dietary fiber, largely based on epidemiological evidence, suggests that they have an essential role in human health. Furthermore, the effects of high-fiber diets on bowel habits have been well known for a long time. Several studies showed the correlations between intestinal transit time (ITT) and fecal wet weight (FWW) and FWW and the consumption of dietary fiber. The FWW could therefore be a basis for determining a recommended intake of dietary fiber to achieve a regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…1) that still continued in 1990, but the amount was calculated to be 18.8g in 1972 and 18.3g in 1975; this was in the same range as in other European countries (Table 1). Furthermore , the TDF intake in 1985 was 17.3g/day, and this was between the recently recalculated values for the French (16g/day) (21) and Dutch (24g/day) (22).…”
Section: Discussionsupporting
confidence: 70%
“…1) that still continued in 1990, but the amount was calculated to be 18.8g in 1972 and 18.3g in 1975; this was in the same range as in other European countries (Table 1). Furthermore , the TDF intake in 1985 was 17.3g/day, and this was between the recently recalculated values for the French (16g/day) (21) and Dutch (24g/day) (22).…”
Section: Discussionsupporting
confidence: 70%
“…Evidence from literature indicated that dietary fiber consumption among Chinese adults aged 18–45 years decreased from 1989 (22.6 g/day) to 2006 (17.8 g/day 37 ), while the trends in the average total dietary fiber intake in Chinese adults aged 45 years and above(19.0 g/day 38 ) remained at a stable level in the past decade in mainland China. In addition, the average daily total dietary fiber intake among Chinese adults aged 45 years and above was higher than that of Western countries such as United States (15.9 g/day 39 ) and France (16.0g/day 40 ). On the other hand, the main dietary pattern of our region is a traditional southern dietary pattern, characterized by high intakes of rice, fresh leafy vegetables, low-fat red meat, pork, organ meats, poultry and fish/seafood and low intakes of wheat flour and maize/coarse grains 41 42 .…”
Section: Discussionmentioning
confidence: 83%
“…In Europe, the estimated national values for dietary fiber intake were found to fall within a narrower range: 16 g/day in France [329], 22.1 g/day in Sweden [330], 16.7–20.1 g/day in Finland [331], 21 g/day in Germany [332], and 20–22 g/day in the Netherlands [333]. An exceptionally high intake level of fiber was found in Switzerland, 30–33 g/day, reflecting a positive trend in the eating habits of this population [334].…”
Section: Beta Glucan-fortified Foods In the Marketmentioning
confidence: 99%